Analisis Penerapan Pengungkapan Global Reporting Intiative (GRI) 400 dalam Sustainability Report pada Sektor Healthcare di Bursa Efek Indonesia Tahun 2024 - Zul Azmi; Emi Vita Liani; Santika Santika; Sri Cahyani (Al-Manar Journal of Accountancy and Business Studies, 2026)
This study aims to analyze the implementation of Global Reporting Initiative (GRI) 400 disclosures in Sustainability Reports in Healthcare sector companies listed on the Indonesia Stock Exchange (IDX) in 2024. The research method used is a qualitative descriptive approach with technical content analysis of the sustainability reports of sample companies. The sample determination was carried out using a purposive sampling method based on the availability of sustainability reports and the application of GRI standards, the research instrument using a GRI 4 indicator checklist that covers economic, environmental, and social dimensions. The results show that the level of disclosure of Healthcare aspects is still relatively suboptimal. The recapitulation of indicators shows that 66.03% of indicators are not disclosed, while full disclosure only reaches 30.14% and partial disclosure 3.83%, this indicates that sustainability practices in the healthcare sector are still selective and tend to focus on administrative aspects that do not fully reflect the completeness.